Identities Management as a Solidarities Constructing Tool in Contemporary Society - Tuzikov, Andrey R.; Zinurova, Raushaniia I.; Alekseyev, Sergey A.; Gayazova, Elvira B.; Ilyasova, Fania F.; Lisina, Olga V. (International Review of Management and Marketing, 2016)
The relevance of the problem stated in the paper is conditioned by the fact that in the contemporary world and in Russia particularly, there is an acute problem associated with the identities' management of members of society. This problem is of particular importance for young people socialization's management. The purpose of this paper is to analyze the theoretical approaches to the identities' configuration management through a combination of conceptual provisions of the theory of management, theory of ideology, sociological and socio-psychological dimensions of identity. The leading approach to the study of this problem is a phenomenological approach allowing presenting as a challenge the construction of a civil ideology that combines social groups' multiple identities, including ethnic and religious ones. The article reveals the heuristic potential of the ideology theory and the solidarities' concept for the specification of multiple identifications of young people in modern societies. The ideological dimension of identifications brings to the representation and legitimacy of group interests. Theory of solidarities allows evaluating the possibilities of identities' different configurations emergence among youth groups. The paper submissions can be interesting both for scientists and for practitioners in the fields of management and education. Keywords: Management of Identities, Social Groups of the Youth, Ideology, Theories of Ideology, Sociocultural Approach JEL Classifications: I21, I25, I28